PERANCANGAN USULAN PERBAIKAN INBOUND LOGISTICS PROCESS GROUP DENGAN MENGGUNAKAN PENDEKATAN DMAIC DAN MULTI MOMENT ANALYSIS - Arif Saefurrohman, M.
The growth of the business field for the basic metal industry in Indonesia requires metal industry business actors to make improvements in order to be able to compete with their competitors. The object of study for this thesis is a company engaged in sheet metal manufacturing and fabrication. Management has an agenda to make improvements in order to increase company profits. Profit increase will be carried out by reducing costs. One indication of the need to reduce costs is the trend of increasing overtime in the Logistics Division during the period 1 July 2022 to 26 January 2023. Management wants to improve inbound logistics in the Logistics Division. Data shows that 66% of overtime activities are overtime for inbound logistics management. Management wants to know the actual processes that occur on the factory floor for inbound logistics management. The existence of overtime indicates that there are activities or tasks that are not added value or waste. In the concept of lean thinking, waste is something that needs to be eliminated. The DMAIC approach is used in this research to improve processes and reduce waste. DMAIC is a process improvement framework that has five phases: Define, Measure, Analyze, Improve and Control. In the Measure phase, measurements are taken by collecting data using the Multi Moment Analysis (MMA) method. MMA is a sampling method that measures the occurrence of tasks, activities, or processes. At the Improve stage, several improvement proposals were designed which consisted of inspection sheet digitization applications, making checklists to optimize the company's 5R agenda, making daily work target sheets for each worker, peer computer training for inputting inbound logistics data, making Standard Operation Procedures (SOP) for reporting differences in material use actions, and changing raw material identity labels by integrating two identity labels. This proposed improvement estimates a reduction in the level of waste by 81,74% man hours from non-value-added work and 1,07% man hours from necessary non-value-added work. The estimated savings from reducing the level of waste are equivalent to Rp. 23,948,597.8 / year.